2019
DOI: 10.15560/15.1.131
|View full text |Cite
|
Sign up to set email alerts
|

New southernmost record of the European Brook Lamprey, Lampetra planeri (Bloch, 1784) (Agnatha, Petromyzontidae)

Abstract: We report the occurrence of the European Brook Lamprey, Lampetra planeri (Bloch, 1784), in the Lao river in the Calabria region (southern Italy). This record extends the species’ known distribution limit southwards. Information regarding some morphometric and ecological data are provided and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…They caught two such specimens on October, 26 2018 with an electro sher (total length 170 and 175 mm). It is clear from the photo of the specimen with the silvery coloration (P. 133, and the gure in [34]) that it is not an adult but a post-metamorphic immature specimen (secondary sexual characteristics are absent). Most probably, it was a smolt of the European river lamprey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They caught two such specimens on October, 26 2018 with an electro sher (total length 170 and 175 mm). It is clear from the photo of the specimen with the silvery coloration (P. 133, and the gure in [34]) that it is not an adult but a post-metamorphic immature specimen (secondary sexual characteristics are absent). Most probably, it was a smolt of the European river lamprey.…”
Section: Discussionmentioning
confidence: 99%
“…Their silvery coloration is characteristic of post-metamorphic juveniles (transformers, macrophtalmia) during their downstream migration [31][32][33]. Sperone et al [34] found what they took to be the southernmost resident population of the European river lamprey (they call it the European brook lamprey L. planeri) in the Lao River (Calabria, Italy). They caught two such specimens on October, 26 2018 with an electro sher (total length 170 and 175 mm).…”
Section: Discussionmentioning
confidence: 99%